2021
DOI: 10.1021/acsami.0c18420
|View full text |Cite
|
Sign up to set email alerts
|

Efficacious CO2 Photoconversion to C2 and C3 Hydrocarbons on Upright SnS–SnS2 Heterojunction Nanosheet Frameworks

Abstract: In this work, SnS–SnS2 heterostructured upright nanosheet frameworks are constructed on FTO substrates, which demonstrate promising photocatalytic performances for the conversion of CO2 and water to C2 (acetaldehyde) and C3 (acetone) hydrocarbons without H2 formation. With post annealing in designated atmospheres, the photocatalytic activity of the SnS–SnS2 heterostructured nanosheet framework is critically enhanced by increasing the fraction of crystalline SnS in nanosheets through partial transformation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Layered bismuth oxyhalides (BiOX, where X = F, CI, Br and I) were used for the conversion of CO 2 with H 2 O without adding photosensitizers or sacrificial agents [123] . The optimal BiOBr photocatalyst displayed CO and CH 4 production rates of 21.6 and 1.2 μmol•g -1 •h -1 , respectively, under simulated sunlight irradiation.…”
Section: Nitride-based Photocatalystsmentioning
confidence: 99%
“…Layered bismuth oxyhalides (BiOX, where X = F, CI, Br and I) were used for the conversion of CO 2 with H 2 O without adding photosensitizers or sacrificial agents [123] . The optimal BiOBr photocatalyst displayed CO and CH 4 production rates of 21.6 and 1.2 μmol•g -1 •h -1 , respectively, under simulated sunlight irradiation.…”
Section: Nitride-based Photocatalystsmentioning
confidence: 99%
“…Although their good photocatalytic activities have been reported, both CaFe 2 O 4 -based and Ca 2 Fe 2 O 5 -based photocatalysts have not been previously investigated for photocatalytic CO 2 conversion in a gaseous system. The efficiency of CO 2 photocatalytic conversion is determined by factors of light harvesting, photocharge separation and transport, as well as CO 2 adsorption and surface reaction taking place on the photocatalysts. , Moreover, the direct reduction of water to hydrogen by photoelectrons is a competitive reaction with the photocatalytic conversion of CO 2 in the presence of water. Therefore, improvement of the selectivity of photoelectrons for CO 2 conversion is crucial to enhance the performance of the photocatalyst for CO 2 photocatalytic conversion. Xie et al reported that the reduction of water to hydrogen was suppressed and the selectivity of formation of CH 4 in CO 2 photocatalytic conversion was improved by the addition of MgO into the Pt–TiO 2 photocatalyst, resulting from enhancements of both CO 2 chemisorption and electron density on the surface of the MgO–Pt–TiO 2 catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Bi et al demonstrated the Li 2 TiO 3 /TiO 2 heterostructured photocatalyst with ∼100% selectivity for CO 2 photoreduction toward CO, which was achieved by increasing the CO 2 adsorption and the photocharge separation with the introduction of Li 2 TiO 3 . Accordingly, suitable surface sites for the preferential adsorption of CO 2 coupling with the fast transfer of multiple electrons to the adsorbed CO 2 are essential for the efficacious photocatalytic conversion of CO 2 . …”
Section: Introductionmentioning
confidence: 99%
“…The converted SnS possesses CO 2 adsorption sites with significantly reduced activation energy, which can be used to drive the rate-determining step for efficient CO 2 conversion. The final Z-scheme SnS-SnS 2 heterostructure enhances the photocatalytic activity of CO 2 conversion to C2 and C3 hydrocarbons [18]. Wu et al constructed a novel direct Z-scheme g-C 3 N 4 /SnS 2 heterojunction by in situ deposition of SnS 2 quantum dots onto the g-C 3 N 4 surface by a simple one-step hydrothermal method.…”
Section: Introductionmentioning
confidence: 99%